Avaliação do diagnóstico de depressão realizado por médicos da Atenção Primária à Saúde de Anápolis - Ana Carolina dos Santos Torquato; Bianca Ganzarolli de Souza dos Santos Oliveira; Cristiana Marinho De Jesus França; Deon Vinícius Moreira Pimentel; Fernanda Vale Guimarães; Talita Braga; Valter Luiz Moreira de Rezende (UniEVANGÉLICA, 2018)
Objective: The Primary Health Care (PHC) has great influence on the prognosis of depression, because it contains representative indices of the population with Major Depressive Disorder (MDD), and therefore critical diagnosis and correct conduct. This study is to knowhow it is addressed major depression by doctors of the Anapolis APS, researching what tools are used for diagnosis, checking if it has been done properly and what theoretical basis / practical / scientific is used, investigating conduct and management adopted in patients with the disorder. Methods:For this, we used a structured questionnaire, that was completed by the respondent, with the purpose of evaluating the knowledge of diagnostic and management criteria. Results:Regarding the theoretical basis (theoretical background)about TDM, 50% have their knowledge gained from books and 17.5% use the DSM 5. Were used, as criteria for the diagnosis of depression, hallucinations, by 22.5% of physicians, sleep changes and lack of energy by 70%. Of the professionals, 15% indicated as the criteria used to diagnose, other disorders of mental health. With respect to the management and conduct adopted by physicians, 12.5% refer all cases, 27.5% feel totally safe to treat and 33.3% feel completely safe in handling cases of depression with the psychiatrist. The results indicate that a considerable proportion of clinical health primary network diagnose and handle this disorder improperly, ascertained through the conceptual errors, lack of foundation and use misleading and confusing diagnostic criteria, suggesting that diagnosis of depression has been done through empirical knowledge and not by Evidence-Based Medicine.